Det ambivalente kvindebillede i danske ordsprog - Archutowski, Tomasz (Folia Scandinavica Posnaniensia, 2020)
The aim of the paper is to identify the image of a woman coded in Danish proverbs. The basis of my research is the assumption that proverbs convey knowledge of how societies perceive the reality and that proverbs are used as interpretative mechanisms. This is mainly achieved thanks to the repetitive nature of proverbs. Simultaneously proverbs force certain perception of the world upon societies and promote certain values. The image of a woman in the Danish language is composed by two stereotypes, a negative and a positive one. The image is a combination of contradictions. On one hand there is admiration for features such as care, motherhood, life experience and, hard work, but on the other hand women are submitted to discrimination and harsh social pressure. Women are depicted as talkative, dominating, evil, vain, unpredictable, unrestrained. They face pressure to get married, take good care of their looks, or be exemplary housewives. The analysis of Danish proverbs gives a possibility to observe how much women’s social status, character and the perception of women by the society have changed throughout the centuries and how these changes have influenced the language we use and the reality that the language depicts.